Analisis Kontribusi Penerimaan Pajak Hotel, Restoran dan Hiburan sebagai Upaya Peningkatan PAD di Kota Surabaya - Anisa Anisa; Ratih Dewi Titisari Haryana (CV. Ulil Albab Corp, 2024)
To establish broad, real, and responsible regional autonomy, regional taxes are one of the important sources of regional income. Possible sources of regional expansion must be carried out as much as possible, of course within the limits of applicable laws and regulations, including regional taxes, which have long been the main component of Regional Original Income. The aim of the research is to determine the influence revenues of hotel tax, restaurant tax and entertainment tax on PAD (Regional Original Income) in Surabaya City. The research used quantitative research with data obtained from scientific journals, books, or other sources. Secondary data taken in this research comes from the official website of the Surabaya City Government and other related agencies who often publish data and statistics on their websites for the 2011-2021 period. Analysis uses multiple linear regression. Based on test, the result show that revenues of hotel tax, restaurant tax and entertainment tax have a positive significant effect on PAD (Regional Original Income).